Gambling-Free Campus: Systematic Literature Review on Prevention and Supervision Strategies - Juana Juana; Kamaruddin Sellang; Hardianti Hardianti (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze strategies for preventing and monitoring online gambling within university settings, providing a comprehensive overview of approaches that can be applied in higher education institutions. Methodology: A Systematic Literature Review (SLR) was conducted on 500 scholarly articles retrieved from the Dimensions database. Data were analyzed using VOSviewer to map research trends and identify key strategic approaches. Results: The analysis reveals three primary strategies: experiential-based education, strict regulatory measures, and technology-based surveillance. Educational strategies enhance digital literacy and awareness campaigns, regulatory strategies restrict access to online gambling platforms, and technology-based approaches employ network monitoring and early detection systems. Conclusion: The findings suggest that a multi-dimensional approach combining education, regulation, and technological monitoring is essential for creating gambling-free campuses. These strategies are mutually reinforcing and can provide a framework for effective prevention and supervision. Limitation: This study is limited to articles sourced from the Dimensions database, which may restrict the global generalizability of the findings. Contribution: This research contributes to public administration and higher education policy by offering a roadmap for developing evidence-based strategies to mitigate online gambling within university environments.